Strategi Pemasaran Perusahaan Wong Solo Dalam Meningkatkan Pendapatan Setelah Masa Pandemi Covid-19 - Ajib Romadhona (ScidacPlus, 2023)
Wong Solo Company Marketing Strategy to Increase Revenue After the Covid-19 Pandemic.” The background to the restaurant business experiencing a decline in income is the Wong Solo restaurant business. The Wong Solo restaurant business is a restaurant business that is well known in Indonesia. This restaurant, which is synonymous with chili sauce, has many branches in various large provincial areas, one of which is in Palembang, South Sumatra. The aim of this research is to find out the marketing strategy for Wong Solo restaurants to increase income after the Covid-19 pandemic. This type of research is qualitative research. Data collection techniques include observation, interviews and documentation. Then the data analysis technique uses data reduction, data presentation and drawing conclusions. The research results show that the Wong Solo company's marketing strategy in increasing revenue after the Covid-19 pandemic is carried out by ensuring a 4P system starting from the product: it must be of higher quality and superior among buyers, then price: food package menus so that it creates interest. Strategic place from the Palembang city branch. Then promotion is carried out widely, covering aspects both through social media and directly through word of mouth. Using 4P as a promotional step in addition to getting lots of customers and increasing revenue after the Covid-19 pandemic.